A whole-of-government approach : lessons from the Philippine counter-insurgency - Taharuddin Piang Ampatuan (2009)
The Philippine counter-insurgency bears a lesson for the whole-government approach. It has all the elements for a successful counter-insurgency: diplomatic and legal offensives, citizen’s diplomacy, effective military strategy and the effective use of government institutions. However, the Philippine insurgency also shows that the success is temporary if the overall political solution is missing.